Vital signs, 2007-2008 : the trends that are shaping our future - Assadourian, Erik.; Anderson, Molly D. (Molly DelCarmen), 1955-; Starke, Linda; Worldwatch Institute (New York : Norton, 2007)
Analyzes twenty-seven key indicators that track trends that are shaping Earth's future, covering the areas of food and agriculture, energy and environment, society and economy, transportation and communications, and conflict and peace for the year 2006, and includes a selection of related essays.
"Worldwatch Institute."
Includes bibliographical references (p. 127-161).
Adult
Keywords: Economic forecasting; Environmental policy